THE POLITICS OF QIRA’AT: STATE POWER AND THE CANONIZATION OF QUR’ANIC RECITATION IN EARLY ISLAM - Khodijah, Siti; Iffah Muzammil; Rafly Try Ramadhani, Moch. (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
The study of qira’at in Islam has traditionally centered on linguistic and phonetic dimensions. However, it also intersects significantly with the dynamics of political authority and canon formation in Islamic history. Using a historical-analytical approach, this study examines the role of political power in the codification and standardization of qira’at, focusing on critical episodes such as the compilation of the mushaf under Caliph ‘Uthman ibn ‘Affan, administrative interventions during the Umayyad dynasty, and the canonization of the seven qira’at by Ibn Mujahid, later expanded to ten by Ibn al-Jazari. Drawing on classical Islamic sources and contemporary academic literature, the study demonstrates that qira’at orthodoxy was shaped not only by scholarly consensus, but also by strategic political interventions in response to socio-political imperatives. By exploring the intersection of religion, power, and the construction of Qur’anic recitational authority, this research contributes to a deeper understanding of how the political construction of religious orthodoxy and the canonization of sacred texts in Islam.